The Advantages of Administrative Reforms in Judicial System, Democracy Transparence and the Rule of Law (Comparative Analyze in Albanian Legal Case Study) - Dumi, Alba Robert; Ngucaj, Neshet (Richtmann Publishing, 2013)
The European Union has offered autonomous trade concessions to the Balkan countries. All industrial products and mostagricultural products have duty and quota free access. â€œAutonomousâ€ means that the European Union immediately opens theinternal market, while a longer period of transition is conceded to the Balkan countries before opening up their markets to EUcompetition. Albanian economic performances have improved recently. But encouraging signs of economic development arebeing at risk by various uncertainties and deficiencies in the Albanian development system. Electricity shortage is a majorhandicap of the country. Many working hours are getting lost when electricity is switched of. This increases costs of productionand business management. Infrastructure - traffic and transportation - is a problem, which particularly impedes economicdevelopment and investment in the more remote and rural regions. Regional development is considered a high priorityobjective by most experts. There has been moderate progress in judicial reform, which is a key priority of the Opinion. Thisarticle presents a summary of the influences of technical assistance and administrative capacity in development of Albaniangovernment. In the centre of this study we are using the concepts and innovations of the E-Learning, which is gainingsignificant interest in distance education, including reforming political, social and economical developing in Albaniangovernment reforms and other details.